STUDIUL ANTROPOLOGIC AL ALIMENTAȚIEI: CADRU TEORETIC ȘI PRACTICI SOCIALE - Bezedica, Eugeniu (CEP USM, 2019)
From a cultural point of view, food gives us many clues about how human society has evolved. Globalization has brought about a new possibilities in access to certain products or ingredients along with exacerbated control over the actors in the food market, with the appearance of an abundance and diversity of food. Effects on population health and cultural diversity nowadays are very visible and it will be interesting to track their evolution.
Keywords: antropologie